ANALISIS KRITIS TERHADAP GERAKAN NASIONAL LITERASI DIGITAL DALAM PERSPEKTIF GOOD GOVERNANCE - Dadan Kurnia (Universitas Jenderal Ahmad Yani, 2021)
The paper analyzes the analysis of the National Digital Literacy Movement (GNLD) from the perspective of good governance with qualitative methods. This analysis is motivated by the pros and cons of GNLD. Those who view this movement as good at fighting hoaxes, fake news, fake news or other negative content that are judged by the wider community. Meanwhile, those who assess the assessment, this movement is an attempt by the government to lead public opinion to legitimize and silence voices criticizing government policies. Analysis of the conclusions of GNLD in the perspective of good governance that GNLD is a government effort to provide security services as well as members of the public in surfing in cyberspace.